Revisiting gender and reproductive health analyses in a global age (2005)
This paper examines the extent that scholars are analysing gender and reproductive health issues in a global era. The examination is necessitated by existing data which indicate that African researchers are investigating these phenomena as static and monolithic. Their approach fails to view the concepts as embedded in complexity and as such require careful decomposition. It has, therefore, become necessary to deviate gender and reproductive health studies from traditional disciplinary insulation that secludes academic fields from other areas of knowledge. The present paper argues that a holistic analysis of gender and reproductive health issues is only achievable with interdisciplinary collaboration and in the context they are reviewed. Transdisciplinary analysis in this study involves understanding gender relations as a way of investigating whether household decisions are both democratic and all inclusive. By emphasising the inseparability of gender and reproductive health discourse, the paper makes important contributions to the theoretical and methodological interests of social research and advances insight on how scholars can adjust, analytically, to changing societies without at the same time infringing on the norms of the academic community.